The Perception of Identity in Territorial Governance: The Italian Case Study of Alto Mantovano Area - Arrighi, Carlo (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
The article collects and illustrates the results of the analysis on the perception of the Alto Mantovano identity, attempting to reconstruct it through the oral testimonies of territory privileged users, the Mayors. The text is structured in three directions. Firstly, an attempt will be made to identify the Alto Mantovano area, highlighting the difference between definitions “from above” and definitions “from below”. Secondly, the focus will examine the historical development of this area, as it is perceived, pointing out how this territory has stratified a specific identity which is proposed as an alternative to that of the main town, Mantua. Finally, it will focus on both similar and divergent points between the realities involved, giving three examples to prove that heterogeneity is possible even if there is the same identity recognition.